SOSIALISASI PEMANFAATAN SUMBER DAYA ALAM BERKELANJUTAN DI KAWASAN EKOWISATA MANGROVE LUPPUNG MANYAMPA - Andira, WAhyu; Azrini, Azrini; Akbar, Fauzan (Bina Bahari, 2023)
Luppung mangrove environmental tourism located in the Bulukumba Regency area has become one of the tourist destinations that has started to be crowded with visitors. In the utilization of resources in mangrove areas, the participation of all parties is required so that their sustainability can be maintained. The purpose of implementing community service is to provide counseling and information to the people of the Luppung mangrove area in the utilization of biological resources in the area. The socialization was held in November 2021, attended by 22 residents of the mangrove area of Luppung Village. PKM activities are carried out using the lecture method and demonstration of video playback for participants who attend. The results of the activity showed that participants' understanding increased in terms of utilizing mangrove plants as an effort to improve the economy without exploiting the environment.